Social Studies Teachers’ Assessment of Introduction of Civic Education as Extra burden in Senior Secondary Schools in Ilorin - Balogun, Idayat Nike; Yusuf, Abdulraheem (NIU Journal of Humanities, 2018)
Effective teaching and learning of and the realization of the objectives of Civic Education in Nigeria Senior Secondary Schools depends on the level of teacher’s ability and efforts put in place by them in terms of effectiveness and efficiency. Readiness of teachers to take additional responsibility in their area of calling is part of what is required of a teacher to accomplish the evidence of students’ learning experience. Teachers’ role remains very important to the successful implementation of senior secondary school civic education as they are saddled with the responsibility to enrich the contents of the subject with relevant information from their immediate environment by adapting the curriculum to their needs and aspirations. This study intends to investigate the teachers’ assessment of introduction of civic education on senior secondary schools in Ilorin as extra burden. A descriptive research design was adopted for this study; the target population for this study was purposively drawn and comprised of 144 respondents. Researcher designed questionnaire was used to collect data and were analyzed with Mean, standard deviation, percentages and t-test statistics at 0.05 alpha level. The findings of this study revealed that to some extent civic education teachers adopt the items listed in the questionnaire for their teaching and they do not perceive the teaching of civic education as burden especially in private school. Based on these findings, it was noted in this study that all schools have the potentials of providing the best. It was on the basis of these findings that the researchers recommended that Civic education should be considered as a subject which should be handled with a more holistic approach to better off the achievable objectives of the subject, teachers’ morale should be boosted regardless of school type and school location so as to sustain significant teaching-learning achievement. Keywords: Public schools, Private Schools, Specialist teachers, Non-specialist teachers, concept of civic education.